IMPLEMENTATION OF TOLERANCE VALUES IN THE CIVICS SUBJECT CASE STUDY AT SANGARI ELEMENTARY SCHOOL, DONGGO DISTRICT - Junaidin; Syufatul; Muliyadin (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study aims to describe the implementation of tolerance values in the learning of Pancasila and Civic Education (PPKn) at SDN Sangari, Donggo Pagi Subdistrict. Tolerance values are an essential part of character building for students, especially at the elementary school level, which serves as the initial foundation in shaping attitudes of mutual respect, appreciating differences, and living harmoniously in diversity. This research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The subjects of the research were PPKn teachers and fourth-grade students at SDN Sangari. The findings indicate that the implementation of tolerance values in PPKn learning is carried out through the integration of teaching materials, teacher role-modeling, habituation of tolerant behavior in school life, and the resolution of simple conflicts among students. Teachers actively instill tolerance through classroom discussions, educational games, and the strengthening of Pancasila values in daily life. However, several obstacles were encountered, such as limited contextual learning media and insufficient teacher training in developing integrated character education within the curriculum. Nevertheless, overall, the process of instilling tolerance values at SDN Sangari shows a positive impact in shaping students' attitudes of mutual respect and acceptance of differences. The study recommends that teachers act as facilitators of tolerance values by maximizing support from the school environment and parents to foster tolerance from an early age